Atmospheric Effects of a Relativistic Electron Beam Injected From Above: Chemistry, Electrodynamics, and Radio Scattering - Marshall, Robert A.; Xu, Wei; Kero, Antti; Kabirzadeh, Rasoul; Sanchez, Ennio (Frontiers in Astronomy and Space Sciences, 2019)
We present numerical simulations and analysis of atmospheric effects of a beam of 1~MeV electrons precipitating in the upper atmosphere from above. Beam parameters of 100~J or 1~kJ injected in 100~ms or 1~second were chosen to reflect the current design requirements for a realistic mission. We calculate ionization signatures and optical emissions in the atmosphere, and estimate the detectability of optical signatures using photometers and cameras on the ground. Results show that both instruments should be able to detect the beam spot. Chemical simulations show that the production of odd nitrogen and odd hydrogen are minimal. We use electrostatic field simulations to show that the beam-induced electron density column can enhance thunderstorm electric fields at high altitudes enough to facilitate sprite triggering. Finally, we calculate signatures that would be observed by incoherent scatter radar (ISR) and subionospheric VLF remote sensing techniques, although the latter is hindered by the limitations of 2D simulations.